Obama's new climate policy: Opportunities and challenges of climate policy change in the US - Stormy Mildner; Jörn Richert (Stiftung Wissenschaft und Politik (SWP), 2010)
Hopes of fresh momentum in the international climate negotiations were high when Barack Obama was elected president of the United States on November 4, 2008. Even during the election campaign, he had announced plans to reduce US greenhouse gas emissions 80 percent by 2050, to increase the percentage of renewable energies in the energy mix 25 percent by 2025, and to set up a national emissions trading system. It seemed then that 2009 would be a banner year for climate protection in the US: not only did the House of Representatives pass a comprehensive climate bill in June, the EPA and the Department of Transportation also issued a number of new regulations. The US also returned to the table to join serious multilateral negotiations on the United Nations Framework Convention on Climate Change.But after the initial euphoria had subsided, disappointment over the Obama administration's climate policy soon set in. There is disagreement among the parties negotiating the new climate agreement - not just on carbon reduction targets, but also on its basic form. The Europeans and the developing countries adhere to the idea of a binding international treaty. The United States, on the other hand, prefers climate goals that conform to national legislation. It is therefore unsurprising that the negotiating partners at the Copenhagen Summit in December 2009 were unable to agree on a concrete statement of intent.The key questions of this study are: What explains Washington's behavior in the international climate negotiations? What are the chances of real change in US climate policy? The main focus is on the driving forces behind domestic climate policy
Keywords: 320